Fostering Entrepreneurial Skills through Education - Srivastava, Priya (JOURNAL OF INDIAN EDUCATION, 2018)
Over the years, entrepreneurial mindsets have shown to be in the foundation of every vibrant society; a society which has seen inclusive growth without sacrificing any geographical region and improved the standard of living of all its members. While education lies in the foundation of all human development, entrepreneurship is not given the same kind of attention in education as other core subjects. Perhaps entrepreneurship is viewed through a narrow slit of scepticism which equates it with money matters alone, and societies the world over have stressed upon the need to keep ‘students away from money to avoid its corrupting influence’. What is ignored in this approach towards entrepreneurship is the fact that successful entrepreneurs are not the kind of people who are obsessed with acquisition of money, by hook or by crook. But they are people with such personal qualities, which if imbibed by others, can help take their careers or businesses to greater levels of success. These qualities include creativity, sense of initiative, spirit of innovation, challenging the status quo to find better alternatives, drive for advancement and growth, perseverance and courage to face challenging situations, managing and being responsible, ethical, etc. It is therefore the need of the hour to include entrepreneurship education in mainstream education.